Production of bio-oil via hydrothermal liquefaction of empty fruit bunch using zeolite and MCM-41 based catalysts - Nawi @ Mohamed, Nurul Suziana (2020)
Biomass is one of the renewable energy that has been revealing its potential as a substituent for natural fossil fuel recently. Nowadays, converting biomass via hydrothermal liquefaction appears to be another alternative to obtain valuable high energy products and chemical. In this study, oil palm empty fruit bunch (EFB) has been chosen as the source of biomass feedstock for conversion of biomass to bio-oil using HZSM-5 (zeolite) and MCM-41 (Mobil Composition of Matter number 41) as a based catalysts. The different composition of metal promoter barium (Ba), nickel (Ni), lanthanum (La) and cerium (Ce) either mono or bimetal were impregnated into zeolite (denoted as CHZSM5) and further investigated. High acidity properties of Ba and Ni modified CHZSM5 found to be the most effective in catalysing the hydrothermal liquefaction of EFB. Besides, the high surface area and volume ratio of combined two metal promoter (Ba1La2, Ba2Ni1 and Ba2La1/CHZSM5) catalysts were the reasons in the increment in the acidic sites and eventually enhanced the catalytic activity in hydrothermal liquefaction of EFB. Other than that, hierarchical zeolite has been produced with the presence of cetyltrimethylammonium bromide (CTAB) as a surfactant and n-alkane (n-hexane, n-octane, n-decane and n-dodecane) as swelling agent to tailor the formation of hierarchical zeolite with large pore. 1.5 molar ratios of n-alkane significantly reduced the size of nanocrystals formed compared to 1.1 n-alkanes, implying high acidity strength of hierarchical zeolite positively influenced by the size of nanocrystal and impactful in catalyst’s perfomance. This study also revealed the ratio of silica to aluminum, Si/Al = 0.03 gave a great influence to the surface area, pore volume and pore diameter of the synthesized MCM-41 (denoted as CMCM Si/Al 0.03) and proportionally increase the acidity of the final catalyst. The addition of active metal Ni into CMCM Si/Al 0.03 rendered the greater dispersion of the crystals and at the same time induces the acidity of the catalyst. As mentioned above, high acidity and high textural properties of the synthesised catalysts improved the quality of the obtained bio-oil in the catalytic hydrothermal liquefaction of EFB with less oxygenated compounds.